Fast simulation of alternating magnetic fields around a crack in a pipeline system using a dipole model method. (30th January 2014) - Le, Minhhuy; Kim, Jungmin; Vu, Hoanghai; Shin, Kisu; Lee, Jinyi; Dupre, Luc; Geuzaine, Christophe
Abstract This study proposes a method for the fast simulation of the distribution of alternating magnetic fields around internal cracks as well as cracks on the inner and outer diameter surfaces of a pipe. This method, which uses a bobbin‐type magnetic camera to inspect cracks in small‐bore piping systems, is based on a dipole model, allowing for the rapid calculation and storage of data on the distribution of alternating magnetic fields around cracks from a sensor moving inside a pipe. Copyright © 2014 John Wiley & Sons, Ltd.